Assessment of ABCDE approach knowledge among residents and interns in multiple Egyptian hospitals, a cross-sectional study - Mohamed Saad Rakab; Ahmed B. Zaid; Malak Abbas Hamadein; Salma Abbas Hamadein; Mahmoud Abd Elgawad Ashour; Alaa Samir El-Shamia; Dina Ayman Mostafa; Rahma Mogahed Rateb; Marwa Abdelrahman Elashry; Mennat-Allah Mostafa El-Badawy; Rehab Shaheen Bahram Shaheen (BMC Medical Education)
Abstract Background The Airway, Breathing, Circulation, Disability, and Exposure (ABCDE) approach is crucial in emergency care, but there may be variability in adherence among healthcare professionals. Inconsistent application of this approach may lead to variations in patient care quality and outcomes. Identifying the factors influencing adherence can help improve training to ensure more effective application across emergency settings. This study explores the theoretical knowledge of the ABCDE approach among Egyptian resident doctors and medical interns. Methods An online survey was conducted in Egypt targeting resident doctors and medical interns. Statistical analyses were performed using SPSS 26 and Excel, descriptive statistics and association tests were used to measure the relationship between knowledge and demographic factors. Results The study included 422 medical residents and interns, with most in university hospitals. The average knowledge score of 59.1% exposed specific gaps in understanding, emphasizing deficiencies in 12 questions answered by less than 50%. Notably, 49.5% acquired ABCDE knowledge from medical school, while 28.2% had ALS/BLS courses. Encouragingly, 91.2% expressed willingness for life support training. Statistical analyses unveiled significant associations between knowledge scores and both medical practice settings and sources of ABCDE knowledge. Surgeons exhibited the lowest knowledge scores among participants, emphasizing the need for tailored interventions across specialties. Conclusion This study addresses a critical gap in ABCDE approach knowledge among Egyptian resident doctors and medical interns. The study points to the need for focused education, especially for surgeons, to improve emergency care skills and patient outcomes through continued training.